Mamíferos de médio e grande porte na APA Pandeiros MG: inventário e estrutura da comunidade - Pereira, Adriele Aparecida (2017)
The mammals represent about 700 species of Brazilian fauna, 30% of them endemic to Brazil. Considered important members of biodiversity, mammals play key roles in the regulation and structuring of ecosystems. However, they are greatly affected by various pressures arising from human activities, mainly due to the loss and fragmentation of habitat. Thus, knowing the community of mammals of medium and large size and evaluating how it responds to some existing variables in a preserved area, is important for the conservation of biodiversity and for correct management strategies to be taken. Thus, the objectives of this work were to list the medium and large mammal species in an Environmental Preservation Area (EPA Pandeiros) where a deactivated dam is located in an ecotone region of the Cerrado and Caatinga biomes located in the north of Minas Gerais and evaluate the influence of biotic and anthropic variables on the richness, abundance and functional groups of these mammals. For this purpose, medium and large mammal fauna were sampled over a period of 16 months at eleven sampling points, four upstream and four downstream of the dam and three in a flooded area, known as Pantanal Mineiro, where a photographic trap Was installed at each point. In addition, some biotic and anthropogenic variables were collected to evaluate their influence on the mammal community. Twenty species of medium and large mammals were recorded, distributed in 7 orders and 13 families. In addition to the species recorded by photographic traps, three species were recorded by opportunistic observations of trails and footprints (Nasua nasua, Chrysocyon brachyurus and Eira barbara). GLM analysis reveals no influence of biotic and anthropogenic variables on mammalian richness. However, a negative correlation is given by the variable distance from the sampling point to the nearest residence on the abundance and the group of herbivores. With regard to generalists, a positive interference is given by the variable density of trees. EPA Pandeiros is considered a priority area for the conservation of global biodiversity. Therefore, correct strategies as well as the inspection and creation of a management plan are essential practices for the maintenance and protection of the species.